Beyond convergence: Poland and Turkey en route to high income - Martin Raiser; Marina Wes; Ayberk Yilmaz (Central Bank Review (CBR), 2016)
This paper compares and contrasts the policy reform experiences of Poland and Turkey en route to high income. For both countries, globalization has presented unprecedented opportunities to catch up, unleased by integration into European and global markets and the establishment of macroeconomic discipline. These opportunities were reinforced by the creation of economic institutions to strengthen competition and support private entrepreneurship, catalyzed by the convergence process with the European Union. Both Poland and Turkey have shown resilience following the 2008 global crisis, but continued success will require renewed structural reform measures. Dealing with the challenging of aging while at the same time finding a way to sustain productivity growth through greater domestic innovation is shaping Poland's policy agenda. Turkey's structural and demographic potential as well as its strategic location between the markets of Europe and Asia offers attractive value proposition to investors, which could be further enhanced with improvements in business regulations and economic governance.
Keywords: 330; Turkey; Poland; Middle income trap; Economic convergence; Economic liberalization; Economic integration; European institutions